Impact of distributed generation on the Nigerian power network - Taiwo Fasina; Bankole Adebanji; Adewale Abe; Isiaka Ismail (Institute of Advanced Engineering and Science, 2021)
Distributed generations (DG) are being installed at increasing rates, both in developed and developing countries. The increasing number of DG connected to the distribution system could have a significant impact on the power system operation. This paper presents a case study investigating the impact of grid-connected DG on the Nigerian power network in terms of bus voltages and network losses. The results showed that without DG, some of the bus voltage magnitudes of the test system were outside the permissible voltage limit of 0.95pu≤Vi≤1.05p.u. However, with DG connected, the voltage magnitudes were improved to allowable values. The network active power loss was reduced by 12.03% from 85.60MW to 75.30MW. In this way, the power system becomes more efficient and secured.